New insights into the multiferroic properties of Mn3TeO6. (25th January 2017) - Ivanov, S A; Ritter, C; Nordblad, P; Tellgren, R; Weil, M; Carolus, V; Lottermoser, Th; Fiebig, M; Mathieu, R
Abstract: Mn3 TeO6 has a trigonal corundum related structure (space group R 3 ¯ ), and orders in an incommensurate antiferromagnetic (AFM) structure at T N ≈ 24 K. A weak ferroelectric order below T  * ~ 21 K has recently been reported. In order to investigate possible structural changes below T N leading to the observed dipole order, we have performed a detailed study of the crystal and magnetic structures of Mn3 TeO6 using neutron powder diffraction (NPD) in the temperature range of 5–40 K. Complementary low-temperature second harmonic generation (SHG) measurements were performed in order to confirm the reported dipole order at T  * . No change in the rhombohedral symmetry associated with a possible displacive phase transition at T  * was observed in the long-range structural correlations, and it appears that Mn3 TeO6 keeps the same incommensurately modulated magnetic spin structure with the propagation vector k   =  (0; 0; 0.43) in the whole temperature range from 5 to 24 K.